2019
DOI: 10.1002/anie.201908579
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Rich Thermoelectric Sulfides: Size‐Mismatch Effect and Chemical Disorder in the [TS4]Cu6 Complexes of Cu26T2Ge6S32 (T=Cr, Mo, W) Colusites

Abstract: In the present study, we investigate the Mo and W for Cr substitution in the synthetic mineral colusite, Cu26Cr2Ge6S32. Primarily, we elucidate the origin of extremely low electrical resistivity which does not compromise the Seebeck coefficient and leads to outstanding power factors of 1.94 mW m -1 K -2 at 700 K in Cu26Cr2Ge6S32. We demonstrate that the abnormally long iono-covalent T-S bonds competing with short metallic Cu-T interactions govern the electronic transport properties of the conductive "Cu26S32" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…59 An interatomic distance T(2 a )–S(8 e ) ≈ 2.228 Å is reported experimentally in the Ge-based colusite, for full Cr occupancy within the T site. 53,58 Fig. 4b shows the simulation of the interatomic distance T(2 a )–S(8 e ) (T(2 a ): V/Cr site) dependence on the lattice parameter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…59 An interatomic distance T(2 a )–S(8 e ) ≈ 2.228 Å is reported experimentally in the Ge-based colusite, for full Cr occupancy within the T site. 53,58 Fig. 4b shows the simulation of the interatomic distance T(2 a )–S(8 e ) (T(2 a ): V/Cr site) dependence on the lattice parameter.…”
Section: Resultsmentioning
confidence: 99%
“…The colusite compound family has been extensively investigated within the last 8 years for its promising performance, currently achieving the symbolic unity value of zT , ranking it as one of the best TE sulfide materials. Among the preliminary steps to achieve this good performance, the major roles of the synthesis approaches, 48,50,51 pristine composition, 47,52–54 doping, 50,55–58 and defect chemistry 48,54,59 have been reported and systematically correlated to their influences on the intrinsic crystal, electronic and vibrational structures of the material. This deep understanding of the structure/property relationship in the colusite structure-type enabled the possibility of controlling its native versatile transport properties and building a pathway towards the application stage.…”
Section: Introductionmentioning
confidence: 99%
“…Thec omplexes affect the transport properties through their remote action on the symmetry of the surrounding tetrahedra that belong to the conductive network. [119] Therefore,t he symmetry and nature of these complexes should be carefully investigated when engineering new materials for energy production. In the high-performance Cr-Ge colusite Cu 26 Cr 2 Ge 6 S 32 an exceptionally high power factor of 1.90-1.94 mW m À1 K À2 at temperatures between 500 Ka nd 700 K was reported.…”
Section: Structure-property Relationships In Inorganicmentioning
confidence: 99%
“…[43] Thei nvestigation concluded that the occupation of the "interstitial" site by the smaller,m ore electronegative Cr 6+ cation compared with other Group 6elements, led to less distortion of the conductive Cu-S network while modifying the metallicity through the particular nature of Cr-Cu interactions.T he resulting ZT value of 0.86 at 700 Ki s among the highest reported for acomplex copper sulfide.The impact of the "interstitial" cation on the transport properties was later confirmed through the added notion of cation-size mismatch when the interstitial site was statistically occupied by two dissimilar cations. [119] Theconsequence of such cationic disorder in the "interstitial" position is ac lear change in the conduction mechanism of the materials from at ypical acoustic phonon scattering to an ionised impurity-like scattering mechanism, as demonstrated by low-temperature measurements of the transport properties.Asimilar change is also achieved by providing the structure with extra cations to statistically occupy the interstitial tetrahedral sites not belonging to the superstructure position. [113] In addition, Cu 26 Ti 2 Sb 6 S 32 ,t he first semi-conducting compound with the colusite structure,exhibits an intrinsically low lattice thermal conductivity ranging from 1.6 WK À1 m À1 at 300 Kt o 0.6 WK À1 m À1 at 673 K. [44] High-performance TE properties can be achieved by partial substitution of Sb by Ge,with a ZT value of 0.9 reached at 673 K. [44] From these recent investigations on colusites,i ta ppears that the T site is only occupied by ad 0 cation (Ti 4+ ,V 5+ ,N b 5+ ,T a 5+ ,C r 6+ ,M o 6+ , W 6+ ), whereas the associated M site is occupied exclusively by ac ation with ad 10 configuration similar to Cu + (M = Ge 4+ , Sn 4+ ,S b 5+ ).…”
Section: Structure-property Relationships In Inorganicmentioning
confidence: 99%
“…What makes sulfides perspective candidates for TE applications is the high abundance and low (if any) toxicity of the constituent elements in comparison to Bi 2 Te 3 and PbTe. Besides intensively studied tetrahedrites, chalcosite or colusites, there is an increasing interest in electronic and thermal transport properties of AB 2 S 4 thiospinels . The reason for that is the ability of the spinel‐type structure to accommodate different metal elements,, which results in tunability of physical properties e.g., from insulator to metal .…”
Section: Introductionmentioning
confidence: 99%